Unusual stereochemical outcome of radical cyclization: synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ramakrishna, G.; Tejwani, R. B.; Ravindranathan, T.; Kamat, Subhash K.; Rai, B.; Sivadasan, L.; Balakrishnan, K.; Ramalingam, S.; Deshpande, V. H. (Tetrahedron, 2005)
An enantioselective synthesis of (+)-biotin 1 starting from naturally available cysteine is described. The key steps are the unusual stereochemical outcome of radical cyclization of compound 10 to prepare 5,5-fused system 11, and the introduction of C4-sidechain at C-6 in 13 via a Grignard reaction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: biotin; exocyclization; radical cyclization

Multi-component carbon-carbon bond forming Mannich reaction catalyzed by yttria-zirconia based Lewis acid - Ramalingam, S.; Kumar, Pradeep (Catalysis Communications, 2008)
A direct three component Mannich-type reaction of aldehyde, amine, and ketone (without silyl enolates) were efficiently catalyzed by yttria-zirconia based strong Lewis acid in aqueous acetonitrile. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: beta-amino carbonyls; Mannich reaction; multi-component reaction; yttria-zirconia based Lewis acid

Synthesis of alpha-amino phosphonates by three component condensation of carbonyl compound, amine, and dialkyl phosphite using Yttria-zirconia based Lewis acid catalyst - Ramalingam, S.; Kumar, Pradeep (Catalysis Letters, 2008)
An efficient Yttria-zirconia Lewis acid catalyzed one-pot synthesis of alpha-amino phosphonates by three component coupling reaction of a carbonyl compound amine and dialkyl phosphates is described in good to high yield.
Keywords: alpha-amino phosphonates; three component coupling; Yttria-zirconia based Lewis acid catalyst

Yttria-zirconia-based lewis acid catalysis of the biginelli reaction: an efficient one-pot synthesis of 3,4-dihydropyrimidin-2-(1H)-ones - Ramalingam, S.; Kumar, Pradeep (Synthetic Communications, 2009)
Yttria-zirconia-based Lewis acid efficiently catalyzes the three-component cyclocondensation reaction of aldehyde, -keto ester, and urea or thiourea in refluxing acetonitrile to produce the corresponding dihydropyrimidones in high yields.
Keywords: Biginelli reaction; dihydropyrimidone; yttria-zirconia-based Lewis acid

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines